P-P31 Splanchnic vein thrombosis in acute pancreatitis: Incidence, risk factors and long term outcomes. (16th December 2021) - Thejasvin, K; Chan, Sara-Jane; Varghese, Chris; Lim, Wei Boon; Cheemungtoo, Gemisha; Akter, Nasreen; Robinson, Stuart; Sen, Gourab; French, Jeremy; Nayar, Manu; Pandanaboyana, Sanjay
Abstract: Background: There is paucity of data on the incidence, risk factors and role of anticoagulation for splanchnic vein thrombosis (SVT) in acute pancreatitis (AP). Methods: A retrospective review of AP admissions between 2018-2021 across North East England was undertaken. Data on demographics, etiology, severity of AP and SVT was collected. In addition, a selective anticoagulation policy for portal vein thrombosis (PVT) and progressive splenic vein thrombosis was explored. Results: 401 patients were included with a mean age of 57.0 and M:F ratio of 1.6:1. 152 patients developed intestinal oedematous pancreatitis and 249 developed necrotising pancreatitis based on Revised Atlanta criteria (RAC). 109 patients (27.2%) developed SVT of which 27 developed a PVT and splenic vein thrombus, 36 PVT only and 46 splenic vein thrombus only. On univariate analysis, alcoholic aetiology, severe pancreatitis, necrotising pancreatitis with >50% necrosis and elevated CRP at 2 weeks were risk factors for developing SVT. On multivariable analysis, alcohol aetiology (OR 2.6, p = 0.002), and >50% pancreatic necrosis (OR 14.6, p = 0.048) increased the risk of developing SVT . 58 patients received anticoagulation for SVT, with a median duration of 90 days of anticoagulation. Recanalization rates were higher for PVT when compared to splenic vein thrombosis. 6 patients developing bleeding complications whilst on anticoagulation therapy. Conclusions: A third of patients with AP develop SVT, particularly those with severe AP secondary to alcohol and with extensive pancreatic necrosis. A selective anticoagulation policy was associated with improved recanalization rates and fewer bleeding complications.